2007
DOI: 10.2209/tdcpublication.48.199
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Salivary Cytokine Levels in Oral Cancer Patients and Healthy Subjects

Abstract: In order to find informative salivary biomarkers specific to oral cancer we examined expression of 4 kinds of cytokine in saliva. Levels of interleukins (IL-1␤, -6, -8) and osteopontin were measured by ELISA using whole saliva samples collected from 19 patients with oral cancer (9 men, 10 women; mean age, 60.9 years) and 20 healthy persons (15 men, 5 women; mean age, 32 years). Expression of the 4 cytokines was higher in patients with oral cancer than in healthy controls. The difference was significant in IL-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 10 publications
4
80
0
2
Order By: Relevance
“…Cytokines and chemokines have been analysed in patients with OSCC [19][20][21][22][23][24][25][26][27][28][29], and in potentially malignant disorders, most commonly interleukin-6 (IL-6) [19,21,22,[30][31][32][33]. IL-6 is a multifunctional cytokine produced by macrophages, neutrophils, fibroblasts, keratinocytes and endothelial cells [34].…”
Section: Introductionmentioning
confidence: 99%
“…Cytokines and chemokines have been analysed in patients with OSCC [19][20][21][22][23][24][25][26][27][28][29], and in potentially malignant disorders, most commonly interleukin-6 (IL-6) [19,21,22,[30][31][32][33]. IL-6 is a multifunctional cytokine produced by macrophages, neutrophils, fibroblasts, keratinocytes and endothelial cells [34].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported increases in salivary IL-8, TNFa, IL-1, IL-6, basic fibroblast growth factor and IL-1β. 1, 9, 10, 13, 22 in HNSCC relative to normal patients but did not quantify changes post-treatment. The present study quantified cytokines pre- and post-treatment.…”
Section: Discussionmentioning
confidence: 94%
“…6, 21 Eight cytokines, TNFα, EGF, GROα, IL-1α, IL-1β, IL-6, IL-8, and VEGF were analyzed because these cytokine are secreted in saliva from HNSCC patients 9, 1113, 22 and were quantifiable concurrently in a multiplex assay. The concurrent increase in IL-6 and IL-8 in post-treatment saliva suggests a common regulatory mechanism, such as NF-κB, which plays an important role in development and progression of HNSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, more than 100 potential OSCC salivary biomarkers have been reported in the literature, based mainly on comparing the levels found in OSCC patients to the levels found in non-OSCC normal controls. Most categories of Potential salivary biomarkers for oral cancer detection are : Non-organic compound (Na, Ca, F, and Mg) [43], peptid (Defensin-1) [44], proteins (IL-1, IL-6, IL-8, TNF-α, Endothelin-1,...) [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59], DNAs ( P53 gene codon 63,…) [60,61], mRNAs (IL-1β, H3F3A,…) [62], Oxidative stress-related molecules (Glutathione, Peroxidase,…) [26], Glucocorticoid (Cortisol) [63], Metabolomics (Lactic acid, Valine,….) [64], Glycosylation related molecules (Sialic acid, α-L-fucosidase) [65,66].…”
Section: Salivary Biomarkersmentioning
confidence: 99%